Evaluation of acetylator phenotype of isoniazid among tuberculosis patients in delta state Nigeria: update on management of toxicity - Nwose, Ezekiel U.; Aganbi, Eferhire; Onyia, Innocent C. (International Journal of Research in Medical Sciences, 2017)
Background: In 1996, acetylator phenotype of thirteen consenting tuberculosis patients who were being treated with isoniazid was briefly examined as part of an MSc biochemistry program. Initial agenda were to determine the half-life of isoniazid and evaluate potential toxicity associated with long-term treatment regimen. This report presents findings of the study, but with the aim of providing an update on diagnosis and monitoring of the treatment of tuberculosis by laboratory methods. Methods: Firstly, the report submitted for the award of MSc Biochemistry was reviewed and reformatted. Secondly, a follow up survey was performed to determine the current practice at the general hospital and ‘tuberculosis and leprosy’ referral centres where the original study was carried out. Thirdly, a brief literature review was performed for any potential update on clinical practices. Results: The study has shown that 53.8% of patients are fast acetylators (t½<2 hr), 30.8% are intermediate acetylators (t½: 2.0–2.5 hr), and 15.4% are slow acetylators (t½>2.5 hr). The follow-up on current practice indicates that molecular technology has been introduced, but limited to susceptibility testing. Whether a patient could be a fast acetylator (requiring long term drug regimen) or slow acetylator (deserving short term drug regiment) is very much appreciated, but test is neither available, nor considered. Conventional diagnostic indices applicable for clinical laboratory monitoring in a drug-responsive patient in terms of efficacy and toxicity of the treatment are discussed. Conclusions: Development of molecular technology has improved and revolutionized TB diagnosis, especially drug resistance testing. However, it is still limited to being an add-on test to conventional microscopy if a new patient is to be initially investigated for pulmonary TB.